THE RELATION BETWEEN PROSOCIAL IN CHILDREN AND PARENTS ATTACHMENT - Nadia Nisa Islamy; Yusi Riksa Yustiana; Aas Saomah (Universitas Pendidikan Indonesia, 2022)
Prosocial behavior is a positive social action to help others by physically and psychologically without expecting reward. Factor that influences individual’s prosocial behavior is the experience of socializing between the children and parents. Parents influence the intensity of prosocial behavior to the children by forming the quality of relationships between the children and parents. Attachment is a strong emotional relationship developed by the children through the interaction with parents because they have special meaning in the children’s life. The research aims to obtain a general description of prosocial behavior and parental attachment and also the relations between prosocial behavior and parental attachments. The research used a quantitative approach with the correlation method. The research subjects included the whole of population of fourth grade students of SD Mathla'ul Khoeriyah Academic Year 2018/2019 which totaled to 59 students. The results showed that in general the prosocial behaviour of students were prosocial category, parental attachment of students were in the secure category and the correlation test using spearman rho. The value of level correlation is 0,332 which means there was low category the relations between prosocial behavior and parent attachment.